Utilization of Solar Cell-Based Lighting to Support Activities in The Farming Area - Arnold Robert Rondonuwu; Lionel Sumampow; Ariyanti Putri Pamolango; Jovanka Lampus; Dellon Tatambihe (Publikasi Indonesia, 2025)
Inadequate lighting in rice cultivation fields at night poses significant challenges that can reduce farmer productivity, especially during planting and harvesting seasons when extended working hours are crucial. Moreover, insufficient visibility at night increases the likelihood of disturbances from nocturnal pests such as rodents and birds. At the same time, limited access to electricity in the fields hinders the ability to provide adequate lighting. This study is not intended to create off-grid lighting supported by solar panels as a sustainable and energy-efficient alternative application for the land. This research uses a literature review method and a technical analysis of the system's individual components, including solar batteries, controllers, and LED lights. The findings show that this system can theoretically provide lighting for 10-12 hours each night and can operate even in cloudy weather thanks to battery storage. This technology can enhance farmers' safety and comfort during work and can be further developed into IoT-based smart agricultural solutions.